Cumulative effects of spruce budworm and moose herbivory on boreal forest ecosystems. (3rd May 2021) - Leroux, Shawn J.; Charron, Louis; Hermanutz, Luise; Feltham, Janet
Abstract: Ungulate herbivory is a key natural disturbance in many ecosystems. In forest ecosystems, ungulate herbivory often co‐occurs with other disturbances yet there are few studies looking at the cumulative impacts of ungulates and other natural disturbances on forest dynamics. We report on an 18‐year experiment to investigate the combined effects of introduced, non‐native moose and native spruce budworm herbivory on balsam fir forest recruitment and regeneration. Specifically, we measured inputs into early life‐history components of balsam fir dominant boreal forest ecosystems such as seed density, seedbed quality, seedling and sapling height and density, as well as adult density in eight paired moose exclosure and control sites across a spruce budworm disturbance gradient (i.e. no outbreak, recent outbreak, old outbreak) that resulted in closed, partially open and open canopies. Piecewise structural equation models (SEMs) revealed a strong negative effect of spruce budworm disturbance on balsam fir adult density and indirect effects of this budworm disturbance on balsam fir seedling and sapling density mediated through adult density. We observed a similar pattern of budworm disturbance effects on balsam fir seed density with the lowest densities in sites with open canopy, then partially open and closed canopies. As expected, the SEM showed a positive effect of bryophyte seedbed cover on balsam fir seedling density. The SEM showed support for a positive effect of moose exclusion on balsam fir sapling height and density. Specifically, saplings were on average taller and denser in exclosure than control plots and these differences are most pronounced at sites with partially open canopies created by spruce budworm disturbance and undisturbed or closed canopy sites. Overall, we show evidence for cumulative and interactive effects of spruce budworm and moose herbivory on all life stages of balsam fir and such effects are negatively affecting regeneration of balsam fir forests. Human activities are creating conditions that facilitate the expansion and increased impacts of herbivores on boreal ecosystem functioning. A greater understanding of how ungulate herbivory interacts with other disturbances is needed to improve our predictions of forest ecosystem dynamics under global change. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.